Clinico-bacteriological Profile and Outcome of Empyema Thoracis in Children at a Tertiary Care Hospital of Central Nepal - pan, Atanu; Jana, Debarshi (Journal of College of Medical Sciences-Nepal, 2020)
Background: Empyema thoracis (ET) is a serious infection of the pleural space. Despite the availability of broad spectrum antibacterial, improved vaccination coverage and better diagnostic tools, Empyema Thoracis remains associated with high morbidity worldwide. Delay in early diagnosis, failure to institute appropriate antimicrobial therapy, multidrug resistant organisms, malnutrition, comorbidities, poor health seeking behaviour and high treatment cost burden contribute to increased morbidity in children. The available treatment options include intravenous broad-spectrum antibiotics either alone or in combination with surgical procedure (thoracocentesis, chest tube drainage, fibrinolytic therapy, decortications with video assistedthoracoscopic surgery (VATS) and open drainage. Methods: Fifty Children between 1 month to 16 years admitted in the Pediatrics Ward, PICU of College of Medical Sciences, Bharatpur,Nepal. Data analysis was done by SPSS 24.0. Results: Present study found that according to blood culture, 3(6.0%) patients had enterococcus, 40(80.0%) patients had no growth, 2(4.0%) patients had pseudomonas, 4(8.0%) patients had staphylococcus and 1(2.0%) patients had streptococcus. We found that 20(40.0%) patients had done CT scan thorax, 30(60.0%) patients had not done CT scan thorax and 32(64.0%) patients had Amoxiclav first line antibiotic and 18(36.0%) patients had Ceftriaxone first line antibiotic. Conclusions: Suitable antibiotics and prompt chest tube drainage is an effective method of treatment of childhood empyema, especially in resource-poor settings. Majority of the patients progress on this conservative management and have good recovery on follow up.